2017
DOI: 10.1080/00913847.2017.1387022
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of structured exercise in the south Asian population with type 2 diabetes: a systematic review

Abstract: The impact of exercise interventions on south Asians with type 2 diabetes (T2DM), who have a higher T2DM incidence rate compared to other ethnic groups, is inconclusive. This study aimed to systematically review the effect of exercise interventions in south Asians with T2DM. Five electronic databases were searched up to April 2017 for controlled trials investigating the impact of exercise interventions on south Asian adults with T2DM. The PEDro scale was used to assess the quality of the included studies. Eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
0
21
1
Order By: Relevance
“…32,44 In our review, the pooled estimates of TUGT showed no significant improvements in the exercise intervention group, which was inconsistent with a previous study. 21 After conducting sensitivity analysis by removing 1 study which participants were T2DM with DPN, the pooled result of the other studies which participants were only T2DM revealed significant improvements in TUGT and heterogeneity. On this basis, it seems that the effect of exercise intervention on TUGT might be better in T2DM patients than T2DM patients with DPN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,44 In our review, the pooled estimates of TUGT showed no significant improvements in the exercise intervention group, which was inconsistent with a previous study. 21 After conducting sensitivity analysis by removing 1 study which participants were T2DM with DPN, the pooled result of the other studies which participants were only T2DM revealed significant improvements in TUGT and heterogeneity. On this basis, it seems that the effect of exercise intervention on TUGT might be better in T2DM patients than T2DM patients with DPN.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 20 Exercise intervention was considered as a core element for managing T2DM and has been proved to be effective to improve various factors strongly related to T2DM and its complications, such as glycemic control, abnormal blood lipids, physical frailty, functional decline, and quality of life. 21 The guideline from International Diabetes Federation (IDF) for managing older patients with T2DM recommended that older patients with T2DM should have a fall risk assessment when they visit their health care providers annually. 22 Furtherly, this guideline recommended that older T2DM patients should receive exercise interventions with special emphasis, such as endurance training, balance training, and strength training.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise is dose dependent, meaning that people who achieve cumulative levels several times higher than the current recommended minimum level have a significant reduction in the risk of breast cancer, colon cancer, diabetes, ischemic heart disease, and ischemic stroke events [3]. Benefits of physical activity have been reported for numerous outcomes such as mortality [4,5], cognitive and physical decline [5][6][7], glycaemic control [8,9], pain and disability [10,11], muscle and bone strength [12], depressive symptoms [13], and functional mobility and well-being [14,15]. Overall benefits of exercise apply to all bodily systems including immunological [16], musculoskeletal [17], respiratory [18], and hormonal [19].…”
Section: Introductionmentioning
confidence: 99%
“…Overall benefits of exercise apply to all bodily systems including immunological [16], musculoskeletal [17], respiratory [18], and hormonal [19]. Specifically for the cardiovascular system, exercise increases fatty acid oxidation, cardiac output, vascular smooth muscle relaxation, endothelial nitric oxide synthase expression and nitric oxide availability, improves plasma lipid profiles [15] while at the same time reducing resting heart rate and blood pressure, aortic valve calcification, and vascular resistance [20].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular rehabilitation programs (CRP) are able to promote several benefits through physical exercise and educational strategies. 1,2 Despite the beneficial effects, the increase in metabolic demand necessary to carry out physical exercise leads to a series of adaptations in cardiorespiratory and autonomic systems, which can be associated with signs and symptoms appearance. 3,4 Several authors approached this aspect, [5][6][7] and alterations in pulse rate (arrhythmias), fatigue, angina and changes in blood pressure were reported.…”
Section: Introductionmentioning
confidence: 99%